Pengaruh Permainan Maze Angka Terhadap Kemampuan Membilang Anak Usia Dini: Studi Eksperimental di TK - Apriani, Siska; Ilhami, Akmillah (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to analyze the effect of the number maze game on the counting ability of children in group B at Al-Hikmah Islamic Kindergarten, East Oku.Method – The research method used is pre-experiment with a one-group pretest-posttest design. The sample in this study was class B2, which consisted of 10 boys and 5 girls selected using purposive sampling. The data collection tools used were observation, test, and documentation, and data analysis using normality test and t-test. Findings – The result of the analysis shows that there is an influence of the number maze game on the counting ability of children in group B using SPSS; the t-test shows a significance value of 0.0001 < 0.05, which identifies a significant improvement in the children’s counting ability. In the pretest and posttest activities, there was a significant improvement, and it can be concluded that the number maze game has an impact on counting ability. Research Implications – The practical implication of this research shows that the number maze game can be applied in early childhood education as an educational game for an effective learning method in improving numerical understanding. The limitation of this study lies in the small number of samples, so that the results of the study can be generalized to a wide population.